Progress in mid-infrared optoelectronics for high-speed free-space data throughput - Frédéric Grillot; Thomas Poletti; Salvatore Pes (APL Photonics)
Free-space laser communications offer a promising alternative for broadband data transmission in places where fiber optics are impractical. This technology, particularly effective at the 1.55 μm wavelength in the near infrared, also has potential applications in the medium-wave infrared (MWIR, 3–5 μm) and long-wave infrared (LWIR, 8–14 μm) ranges. MWIR and LWIR are superior for transmission through fog, clouds, and dust, with LWIR offering stealth advantages thanks to natural thermal radiation. In addition, mid-infrared wavelengths benefit from reduced atmospheric scattering and signal distortion, making them much more reliable for free-space optical communications. Quantum cascade devices such as lasers, modulators, and detectors operating in the MWIR and LWIR ranges are seen as high-potential candidates for data transmission under poor weather conditions or in degraded environments. This Perspective reviews advances in mid-infrared optoelectronics and their applications in high-speed data transmission and integrated photonic technologies, offering insights for researchers and engineers working in this field.